2008
DOI: 10.1073/pnas.0803183105
|View full text |Cite
|
Sign up to set email alerts
|

Rate-specific synchrony: Using noisy oscillations to detect equally active neurons

Abstract: Although gamma frequency oscillations are common in the brain, their functional contributions to neural computation are not understood. Here we report in vitro electrophysiological recordings to evaluate how noisy gamma frequency oscillatory input interacts with the overall activation level of a neuron to determine the precise timing of its action potentials. The experiments were designed to evaluate spike synchrony in a neural circuit architecture in which a population of neurons receives a common noisy gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…As observed in other recent studies, we found that neurons can become synchronized to a common input (de la Rocha, Doiron, Shea-Brown, Josic, & Reyes, 2007; Ermentrout et al, 2008; Markowitz, Collman, Brody, Hopfield, & Tank, 2008; Tiesinga et al, 2008; Tiesinga & Toups, 2005). These neurons form an ensemble, whose collective postsynaptic impact is enhanced because of synchrony (Salinas & Sejnowski, 2000, 2001; Wang, Spencer, Fellous, & Sejnowski, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…As observed in other recent studies, we found that neurons can become synchronized to a common input (de la Rocha, Doiron, Shea-Brown, Josic, & Reyes, 2007; Ermentrout et al, 2008; Markowitz, Collman, Brody, Hopfield, & Tank, 2008; Tiesinga et al, 2008; Tiesinga & Toups, 2005). These neurons form an ensemble, whose collective postsynaptic impact is enhanced because of synchrony (Salinas & Sejnowski, 2000, 2001; Wang, Spencer, Fellous, & Sejnowski, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, such mechanisms have received experimental support in vitro (McLelland and Paulsen, 2009), and could account for the numerous cases of PoFC observed in vivo (see Table 1). More generally, there is both theoretical (Brette and Guigon, 2003) and experimental (Hasenstaub et al, 2005;Schaefer et al, 2006;Markowitz et al, 2008) evidence that a common oscillatory drive for a group of neurons, periodic or not, improves the reliability of their spike times, by decreasing their Figure 8. Acceptable frequency range.…”
Section: Discussionmentioning
confidence: 99%
“…Subthreshold cellular dynamics, such as spike frequency adaptation 101 or fast membrane tracking of slow synaptic inputs 92 also shape L and hence the transfer of correlation. Increased cellular heterogeneity between the postsynaptic neuron pair typically reduces ρ 38,102 , particularly when measured over short timescales 38,103,104 . These studies all explicitly considered the case of correlation transfer for a neuron pair; however the cellular and synaptic mechanisms that determine the response gain of a neuron have been a long standing topic of interest 105 .…”
Section: Three Mechanisms Of Correlation Modulationmentioning
confidence: 99%